2014
DOI: 10.1039/c4ra10023a
|View full text |Cite
|
Sign up to set email alerts
|

Continuous release of gentamicin from gold nanocarriers

Abstract: Antimicrobial activity of gentamicin can be extended through release from gold nanocarriers after conjugation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Similar kinetic of release were reported from gentamicin conjugated onto the surface of functionalised gold nanoparticles through the formation of ester bonds [12]; this points towards the controlling role of the type of bond on the release kinetic of conjugated antibiotic on surfaces. The functionalisation of the particles had an extreme impact on the loading and desorption of gentamicin, when either amino (positively charged) or carboxyl (negatively charged) were present on the surface more antibiotic was adsorbed onto the surface and the release of gentamicin was almost complete compared to about 10% seen in unfunctionalised silica nanoparticles.…”
Section: Discussionsupporting
confidence: 52%
“…Similar kinetic of release were reported from gentamicin conjugated onto the surface of functionalised gold nanoparticles through the formation of ester bonds [12]; this points towards the controlling role of the type of bond on the release kinetic of conjugated antibiotic on surfaces. The functionalisation of the particles had an extreme impact on the loading and desorption of gentamicin, when either amino (positively charged) or carboxyl (negatively charged) were present on the surface more antibiotic was adsorbed onto the surface and the release of gentamicin was almost complete compared to about 10% seen in unfunctionalised silica nanoparticles.…”
Section: Discussionsupporting
confidence: 52%
“…The rate of this reaction increases further from neutrality, thus leading to the gradually greater release of DEX from pH =7 to pH =4. A similar drug release profile was observed by Nuttelman et al, 52 where DEX was covalently attached to polyethylene glycol-based hydrogel scaffold and for gentamicin when attached to gold 53 and silica. 49 As for mercapto route ( Figure 6B), results showed that DEX presented a less efficient, and with lower drug concentrations, release when compared with amino route.…”
Section: Dex Release Profilesupporting
confidence: 79%
“…The SiO 2 -gentamicin nanohybrids show a weight loss of 2.16% from 100 to ~220°C and a final weight loss (13.70%) from 220 to 500°C. A temperature of ~220°C can be considered as the beginning of gentamicin decomposition, 33 which continued as the temperature increased. The amount of gentamicin in the SiO 2 -gentamicin nanohybrids can be determined by subtracting the mass loss of native SiO 2 NPs from the mass loss of SiO 2 -gentamicin nanohybrids, after precluding the weight loss of water in both samples.…”
Section: Characterization Of the Sio 2 -Gentamicin Nanohybrids And Namentioning
confidence: 99%